Optimization of Ultrasound-Assisted Extraction of Phenolic Compounds from the Aerial Part of Plants in the Chenopodiaceae Family Using a Box–Behnken Design - Sara Lemmadi; Faïza Adoui; Emilie Dumas; Samira Karoune; Cyrille Santerre; Adem Gharsallaoui (Applied Sciences)
This research aimed to optimize the extraction conditions of phenolic compounds by ultrasound-assisted extraction (UAE) from Cornulaca monacantha Del., a species of the Chenopodiaceae family, using response surface methodology (RSM). A three-level Box–Behnken Design was used to investigate the following three factors of extraction conditions: solid-to-liquid ratio (<semantics>Xi</semantics>), extraction temperature (<semantics>Xj</semantics>), and extraction time (<semantics>Xk</semantics>). The optimized UAE extraction conditions obtained were: (<semantics>Xi</semantics>) = 0.5:10 g/mL, (<semantics>Xj</semantics>) = 45 °C, and (<semantics>Xk</semantics>) = 30 min. Once the extraction conditions of the phenolic compounds had been optimized, this protocol was applied to another plant of the same family, Anabasis articulata (Frossk.) Moq. The optimum values of extraction yield, total polyphenol content (TPC), and total flavonoid content (TFC) were respectively 14.68%, 37.27 (µg GAE/mg DE), and 7.21 (µg QE/mg DE) for Cornulaca monacantha Del., and 13.56%, 58.38 (µg GAE/mg DE), and 6.44 (µg QE/mg DE) for Anabasis articulata (Frossk.) Moq. Anabasis articulata (Frossk.) Moq. has a significantly higher antioxidant potential than Cornulaca monacantha Del. due to its high content of phenolic compounds (TPC). The high concentration of these plants in phenolic compounds validates their potential for traditional medicinal use.